Use of Keratin Present in Chicken feather as a Hydrogen Storage Material: A Review (International Journal of Engineering Materials and Manufacture, 2020)
Global warming is the major consequence of pollution. The pollutants that contribute to global warming are commonly known as greenhouse gases. The world has seen an increase in the carbon dioxide concentration over the past few years. The largest sources of carbon emission is the combustion of fossil fuels. The concept of â€œGreen Clean Energyâ€ raised on a mission to reduce the release of these hazardous emissions. Hydrogen is one of those clean energy fuel which helps in solving the present crisis. Materials such as chicken feathers can be used as a medium to store hydrogen. Several research studies are reviewed where chicken feathers are thermally treated by the method of pyrolysis to make them a novel material for hydrogen storage. The uniqueness in the structure and properties of chicken feather is it contains 90% of keratin fibre when heated increases its micropore volume that results in higher hydrogen uptake.